EFECT OF LASERPUNCTURE INDUCTION TO INCREASE GSI AND HSI MALE CATFISH BROODSTOCKS - Hariani, Dyah; Purnama, Erlix Rachmad; Purnama, Tarsan; Fadjar, Mohamad (JFMR (Journal of Fisheries and Marine Research), 2020)
Induction of laser puncture in the male catfish broodstock has a positive influence by increasing reproductive activity which is very helpful for the process of gonadal maturation. The contribution of laser puncture induction in accelerating gonadal maturation can be seen with an increasing in the value of Gonado Somatic Index (GSI) and Hepato Somatic Idex (HIS) indicators. The purpose of this study was to examine the effect of laser puncture induction on increasing the value of GSI and HIS male catfish broodstock. This experimental study used 48 broodstocks of one year old male catfish with a body weight of 1000-1200 g maintained in a concrete pond. The treatment consisted of 2 groups i.e. without induction and induction of laser puncture, each treatment was repeated 4 times. Laser puncture induction was performed every 15 days at the point of reproduction for 15 seconds until the 75th day. The parameters observed were GSI and HIS. The results showed that there was a highly significant increase (P <0.002) in the value of GSI and HSI in male male catfish broodtock after induced by laser puncture. Conclusion for this research was laser punctur induction at the point of reproduction in male catfish can accelerate gonadal maturation with indicators of increasing GSI and HIS values.Â